Memo untuk Najib - Hussien Alattas, Syed (Gombak, Kuala Lumpur : JB News Media Network, 2013)
Criticism on political behavior of Najib Tun Razak, the sixth Prime Minister of Malaysia.
In Malay.
Keywords: Najib Tun Razak, -- Datuk; Prime ministers -- Malaysia -- Conduct of life; Malaysia -- Politics and government -- 21st century